2011
DOI: 10.1094/pdis-10-10-0724
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Spot of Houttuynia cordata Caused by Alternaria alternata in China

Abstract: Houttuynia cordata is a perennial herbaceous plant (family Saururaceae) that is native to southern China, Japan, Korea, and Southeast Asia where it grows well in moist to wet soils. It is commonly used as a Chinese herbal medicine and as a vegetable. In North America and Europe it is also used as an ornamental. From September 2007 to November 2009, symptoms of leaf spot were found on H. cordata leaves in Dangyang County, Hubei, China, with the crop area affected estimated to be over 600 ha per year. Rhizome yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The leaf spot disease was also reported on Hydrangea macrophylla in Italy and Rumex dentatus in Pakistan with occurrence rates over 70% (Garibaldi et al, 2007; Siddiqui et al, 2009). And there have also been a report of this pathogen causing the blackspot disease on Houttuynia cordata in China (Zheng et al, 2011). At present, report on flax black spot in China is rare.…”
Section: Resultsmentioning
confidence: 99%
“…The leaf spot disease was also reported on Hydrangea macrophylla in Italy and Rumex dentatus in Pakistan with occurrence rates over 70% (Garibaldi et al, 2007; Siddiqui et al, 2009). And there have also been a report of this pathogen causing the blackspot disease on Houttuynia cordata in China (Zheng et al, 2011). At present, report on flax black spot in China is rare.…”
Section: Resultsmentioning
confidence: 99%
“…But a few information is available regarding the fungal diseases of the plant home and abroad (Azad andShamsi 2011, Zheng et al 2011). Zheng et al (2011) also reported that symptoms appeared on leaves of H. cordata from September 2007 to November 2009 in Dangyang County, Hubei, China. He also reported the crop area affected estimated to be over 600 ha per year.…”
Section: Introductionmentioning
confidence: 94%
“…The isolated 7 fungi namely Alterneria alternata, Aspergillus fumigatus, Aspergillus niger, Colletotrichum gloeosporioides, Curvularia lunata, Pestaliopsis guepiniand, Rhizopus stolonifer were tested for their pathogenic potentiality. The results revealed that A. alternata and C. gloeosporioides produced symptoms on H. cordata Zheng et al (2011). first reported leaf spot of H. cordata caused by A. alternata from China.…”
mentioning
confidence: 91%
“…But little information is available regarding the fungal diseases of the plant in home and abroad (Azad andShamsi 2011and Zheng et al 2011).Previously it was reported that symptoms appeared on leaves of H. cordatafrom September 2007 to November 2009 in Dangyang County, Hubei, China and the crop area affected estimated to be over 600 ha per year. Rhizome yield was reduced by 20% on average, with up to 70% yield losses in some fields during the autumn growing season (Zheng et al 2011).So far there is no report available regarding the control of the diseases of H. cordata.Present research was undertaken to find out a suitable ecofriendly management of the diseases of this important herbal medicinal plant.…”
Section: Introductionmentioning
confidence: 99%